Linking Deltahedral Zintl Clusters with Conjugated Organic Building Blocks: Synthesis and Characterization of the Zintl Triad [R‐Ge9‐CHCHCHCH‐Ge9‐R]4−1. (29th January 2015) - Bentlohner, Manuel M.; Klein, Wilhelm; Fard, Zohreh H.; Jantke, Laura‐Alice; Fässler, Thomas F.
Abstract: The accessibility of triads with deltahedral Zintl clusters in analogy to fullerene–linker–fullerene triads is another example for the close relationship between fullerenes and Zintl clusters. The compound [K(2.2.2‐crypt)]4 [RGe9 ‐CHCHCHCH‐Ge9 R](toluene)2 (R=(2 Z, 4 E )‐7‐amino‐5‐aza‐hepta‐2, 4‐dien‐2‐yl), containing two deltahedral [Ge9 ] clusters linked by a conjugated (1 Z, 3 Z )‐buta‐1, 3‐dien‐1, 4‐diyl bridge, was synthesized through the reaction of 1, 4‐bis(trimethylsilyl)butadiyne with K4 Ge9 in ethylenediamine and crystallized after the addition of 2.2.2‐cryptand and toluene. The compound was characterized by single‐crystal structure analysis as well asNMR and IR spectroscopy.